Effects of coagulation processes on phytoplankton mortality in the Elbe estuary from a Lagrangian perspective - Steidle, Laurin; Pein, Johannes; Burd, Adrian; Vennell, Ross (Frontiers in Marine Science, 2025)
In the Elbe estuary, a sharp decline in phytoplankton concentration is observed as the river reaches the deep shipping channels of the Port of Hamburg. This collapse significantly impacts the estuarine food web and carbon cycle, shifting the ecosystem from autotrophic to heterotrophic. Previous studies hypothesized that this decline is primarily due to zooplankton grazing. We propose an alternative hypothesis focused on the role of phytoplankton aggregation with inorganic suspended sediments. We present a novel individual-based Lagrangian model of the Elbe estuary. This model couples hydrodynamic, sediment transport, and biogeochemical processes to investigate the influence of aggregation on phytoplankton mortality. By explicitly accounting for the effect of aggregation-induced sinking, our model suggests that over 80% of phytoplankton larger than 50 µm may be lost to light-limitation-induced mortality. Furthermore, the mortality pattern predicted by our model aligns with areas of intense organic matter remineralization in the estuary. These findings underscore the need for estuarine-specific ecosystem models that can capture the complex interplay between physical and biogeochemical processes in these dynamic environments, while demonstrating the potential of Lagrangian methods to provide new insights into the mechanisms shaping estuarine ecosystems.